The contextualized curriculum and young people remaining in the countryside (Research, Society and Development, 2021)
In this article, we address the discussions held at the I International Congress and III National Congress of Social and Education Movements, organized by the Social Movements, Diversity and Education Study Group at the Center of Studies and Research in Education and Human Science at the State University of Santa Cruz (UESC). We present the proposal of Education in the Countryside adopted by the Presidente Tancredo Neves Rural Family House (CFR-PTN), located in the Southern Lowlands region of Bahia, also known as “rotation education”.  We reflect on this institution`s contribution towards valuing the rural environment for the socio-economic, cultural and educational development of young people, their families and communities. In order to construct this reflection, we utilized bibliographic research, which enabled us to gain a general overview of the main work which has been conducted until this time. This provided current and relevant data on the topic of rotation education and the contextualized curriculum. The pedagogy adopted by CFR-PTN, which does not separate practice from theory, favors student autonomy as a central point to enhance their education, clearly showing that when the curriculum is designed for the students, learning becomes more meaningful and enjoyable.